Identification of Important Genes Involved in the Sex-Differentiation Mechanism of Oriental River Prawn, Macrobrachium nipponense, During the Gonad Differentiation and Development Period - Jin, Shubo; Zhang, Wenyi; Xiong, Yiwei; Jiang, Sufei; Qiao, Hui; Gong, Yongsheng; Wu, Yan; Fu, Hongtuo (Frontiers in Genetics, 2022)
Identification of important genes, involved in the gonad differentiation and development, plays essential roles in the establishment of the artificial technique to regulate the process of testis development in M. nipponense. In this study, we aimed to determine the sensitive period of gonad differentiation and development through performing the Hematoxylin and eosin (HE) staining. The important genes involved in the gonad differentiation and development of M. nipponense, were then identified through performing the transcriptome profiling analysis during the sensitive period of gonad differentiation and development. HE staining analysis revealed that the sensitive period of gonad differentiation and development was from post-larval developmental stages 5 (PL5) to PL25, which was dramatically faster than the other identified aquatic animals. Transcriptome profiling analysis predicted that Phagosome, Lysosome, Oxidative phosphorylation, and Glycolysis/Gluconeogenesis play essential roles in the mechanism of gonad differentiation and development in M. nipponense. A total of 29 genes were further identified as the candidate genes, involved in the process of gonad differentiation and development in M. nipponense, based on the gene annotation and gene expression pattern. The qPCR analysis of Mn-JHEH, Mn-DHP, Mn-ALY, and Mn-SMA6 during the whole developmental process revealed that all of these four genes showed high expression levels during the sensitive period of gonad differentiation and development in M. nipponense. Mn-JHEH, Mn-DHP and Mn-ALY showed higher expression at PL25F than that of PL25M, while Mn-SMA6 showed higher expression at PL25M. RNAi was further used to investigate the potential functions of SMA6 in male sexual development of M. nipponense. The RNAi analysis revealed that SMA6 positively regulated the testis development in M. nipponense through affecting the expressions of Mn-IAG. This study provided valuable evidences for the establishment of the technique to regulate the process of gonad development in M. nipponense.